Monitoring of alcohol strength and titratable acidity of apple wine during fermentation using near-infrared spectroscopy. (March 2016) - Peng, Bangzhu; Ge, Na; Cui, Lu; Zhao, Hui
Abstract: Rapid development in apple wine industry has raised a growing need for effective fermentation process monitoring. The alcohol strength and titratable acidity have been used as indicators for process control and optimization in apple wine making. The objective of this study was to investigate the efficacy of using near-infrared (NIR) spectroscopy to monitor and assess the process parameters during apple wine fermentation. A simple and rapid NIR spectroscopy method was developed for simultaneous determination of alcohol strength and titratable acidity in apple wine. The selected spectral regions of 6101.9–5446.2 cm −1, and 11, 995.4–7498.1 cm −1 were pretreated by second derivative (SD) and straight line subtraction (SLS) for alcohol strength and titratable acidity, respectively, prior to developing calibration models using partial least squares (PLS) regression with cross-validation. The highest R c 2 and the lowest RMSECV in the calibration set were obtained for the alcohol strength (0.923 and 4.63 mL/L) and for the titratable acidity (0.930 and 0.264 g/L). The NIR calibration models showed good correlation of determination and low predictive errors. Application of the NIR calibration models demonstrated the feasibility of NIR spectroscopy to be used as a quality control tool for monitoring the apple wine fermentation process. Highlights: A near-infrared spectroscopy method was developed for determination in apple wine. Calibration models showed good predictive ability at optimized condition. Near-infrared spectroscopy can be used for monitoring apple wine fermentation process.